2021
DOI: 10.1021/acsami.1c13732
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Measurements of the Mechanical Properties of Electrochemically Deposited Li2CO3 and Li2O Nanorods

Abstract: Solid-electrolyte interface (SEI) is "the most important but least understood (component) in rechargeable Liion batteries". The ideal SEI requires high elastic strength and can resist the penetration of a Li dendrite mechanically, which is vital for inhibiting the dendrite growth in lithium batteries. Even though Li 2 CO 3 and Li 2 O are identified as the major components of SEI, their mechanical properties are not well understood. Herein, SEIrelated materials such as Li 2 CO 3 and Li 2 O were electrochemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
2
9
0
Order By: Relevance
“…What is worse, the cracks and defects in the SEI layer are regarded as "hot spots" that attract Li + deposition and generate Li dendrites, further deteriorating the electrochemical performance. 37 However, the cycled LiF@ Li and LiF@Li−air anodes display a smooth surface without dendrite observation (Figures 7c,d and S4c,d), which can be attributed to the following reasons (Figure 7e): (1) the dense LiF-rich interfacial protective layer inhibits the side reaction between the inner Li and electrolyte, (2) LiF exhibits excellent Li + diffusivity and chemical stability, which favors uniform Li + deposition and restrains dendrite growth, 38 (3) Li 2 CO 3 represents excellent electrochemical stability and acceptable ionic conductivity to bear volume change and inhibit dendrite growth, 39 (and 4) moreover, the LiF-rich interfacial protective layer consists organic components on the outer surface, affording flexibility and relieving volume change during cycling. 40 As a consequence, a prominent interfacial stability is achieved in Li metal batteries using LiF@Li as an anode.…”
Section: Resultsmentioning
confidence: 99%
“…What is worse, the cracks and defects in the SEI layer are regarded as "hot spots" that attract Li + deposition and generate Li dendrites, further deteriorating the electrochemical performance. 37 However, the cycled LiF@ Li and LiF@Li−air anodes display a smooth surface without dendrite observation (Figures 7c,d and S4c,d), which can be attributed to the following reasons (Figure 7e): (1) the dense LiF-rich interfacial protective layer inhibits the side reaction between the inner Li and electrolyte, (2) LiF exhibits excellent Li + diffusivity and chemical stability, which favors uniform Li + deposition and restrains dendrite growth, 38 (3) Li 2 CO 3 represents excellent electrochemical stability and acceptable ionic conductivity to bear volume change and inhibit dendrite growth, 39 (and 4) moreover, the LiF-rich interfacial protective layer consists organic components on the outer surface, affording flexibility and relieving volume change during cycling. 40 As a consequence, a prominent interfacial stability is achieved in Li metal batteries using LiF@Li as an anode.…”
Section: Resultsmentioning
confidence: 99%
“…Although Li 2 CO 3 contributes to the strong mechanical rigidity of the SEI with a mechanical strength range of 192–330 MPa, its effect on Li-ion transport is still uncertain . Some studies suggest that crystalline Li 2 CO 3 is a typical Li-ion conductor .…”
Section: In-depth Analysis Of Ionic Transport Modeling Across the Seimentioning
confidence: 99%
“…Although Li 2 CO 3 contributes to the strong mechanical rigidity of the SEI with a mechanical strength range of 192− 330 MPa, its effect on Li-ion transport is still uncertain. 155 Some studies suggest that crystalline Li 2 CO 3 is a typical Li-ion conductor. 156 A previous study by Zhang and colleagues demonstrated that doping Li 2 CO 3 with Li 3 PO 4 can enhance its ionic conductivity for temperatures up to 400 °C.…”
Section: Lithium Fluoridementioning
confidence: 99%
“…Consequently, a more stable LiF-and Li 2 CO 3 -rich SEI can be obtained, providing both mechanical strength and improved interfacial Li þ transfer. [32][33][34]…”
Section: Constructing a Robust Sei Throughprelithiationmentioning
confidence: 99%